Emotional education in the educational practice of the preschool teacher - Murillo Suárez, Maria Camila; Gómez Cardona , Liliana María (Rastros Rostros, 2021)
This article is due to a research whose main objective was to understand how the emotional education of the preschool teachers are presented in their educational internship, at the I. E. Rafael Pombo de La Estrella-Antioquia. the investigative methodology was qualitative from the phenomenological paradigm with a transversal descriptive scope, through which the emotional reality of 4 teachers was interpreted; we used data-collection techniques such as, semi-structured interview and participant observation. The results were obtained from some initial categories that are described as the competences that confront emotional education according to Bisquerra’s theory. It concluded that teachers need tools and strategies for handling their emotionality and in their effort to reinvent themselves, the state of mind is variable and they require methods to channel their feelings.
Keywords: early childhood; educational practice; integral assistance; emotional skills; emotional education